Physicians’ Approach to Vaccination Against COVID-19 Infection and Factors Affecting Vaccine Acceptance - Eşkazan, Tuğçe; Candan, Selçuk; Bakkaloğlu, Oğuz Kağan; Yıldırım, Süleyman; Hatemi, İbrahim (Cerrahpaşa Medical Journal, 2024)
Objective: Healthcare professionals play a pivotal role in shaping society’s attitudes towards vaccines. The aim of this study is to assess vaccine hesitancy and acceptance among physicians toward COVID-19 vaccines and to identify the factors influencing their attitudes. Methods: This cross-sectional, web-based survey study, which involved physicians, was designed using Google Forms, and all questions were developed by researchers. The survey consists of two parts, including participants’ sociodemographic characteristics and opinions regarding COVID-19 and the vaccine. Results: The study comprised 602 participants, with 67.6% reporting providing healthcare to COVID-19 patients. Among them, 82.9% perceived COVID-19 as highly dangerous, and 98% recommended vaccination to their patients. There were 25 individuals (4.1%) who had never been vaccinated. Among this group, 60% expressed concerns about the vaccine’s safety and were afraid of potential future side effects. Vaccine supporters (VS) were more likely to perceive COVID-19 as “very dangerous” compared to the anti-vaccine group (AVG). Additionally, the VS showed higher support for vaccination and had a higher rate of receiving the influenza vaccine. The AVG believed the vaccine to be effective but not safe. Factors associated with being in the AVG included not receiving the influenza vaccine, not perceiving vaccines as safe and effective, and not considering the pandemic to be dangerous. Conclusion: Despite the concerns, healthcare professionals, particularly physicians, had the highest vaccination rates. The high vaccination rates and confidence in the vaccines among healthcare workers are positive findings that support the effectiveness of vaccination strategies targeted at this group. Cite this article as: Eşkazan T, Candan S, Bakkaloğlu OK, Yıldırım S, Hatemi İ. Physicians’ approach to vaccination against COVID-19 infection and factors affecting vaccine acceptance. Cerrahpaşa Med J. 2024;48(3):219-227.